Implementation of the Occupational Safety and Health Management System (SMK3) at the Wates Community Health Center in Kediri Regency - Wahyu Purnomo Jati; Rofik Darmayanti (Journal of Hospital Management and Services, 2026)
Risk management in healthcare facilities (fa5msyankes) aims to create a healthy, comfortable, safe, and secure work environment. Therefore, every healthcare facility needs to implement an Occupational Safety and Health Management System (SMK3). The Wates Community Health Center in Kediri Regency has implemented an SMK3 since 2019, making it crucial to conduct research on the system's implementation and the challenges encountered. Objective: To identify the process of policy formulation, planning, implementation, monitoring and evaluation, as well as performance review and improvement efforts, including challenges encountered in implementing the Occupational Safety and Health Management System (SMK3). Subjects and Methods: This study employed a qualitative method with a case study approach. The research subjects included management and the OHS team, while the research objects included the implementation of the SMK3 and its supporting documents. The instrument used was a questionnaire to guide the interviews. Data collection was conducted through interviews, observations, and documentation studies. Results: Internal OHS policies and planning have been established and effectively socialized. Eight OHS standards have been implemented in healthcare facilities. The OHS team routinely conducts monthly monitoring and conducts evaluations every semester. However, no external review or performance improvement efforts have been conducted. Internal obstacles include the workforce's lack of understanding of OHS implementation in healthcare facilities, resulting in incomplete implementation, coupled with limited funding. Externally, a challenge is the lack of support from relevant agencies responsible for overseeing OHS implementation in community health centers..